Basic radar analysis - Budge, Mervin C. Jr; German, Shawn R. (Atech House radar series, 2015)
This authoritative new resource presents fundamentals of radar analysis including the range equation, detection theory, ambiguity functions, antennas, receivers, SP, and chaff analysis for modern radars.